Digitalisasi Layanan Peradilan Agama: Efektivitas E-Court dan Tantangannya dalam Sengketa Hukum Keluarga Islam - Rizka Amelia (CV. ITTC INDONESIA, 2025)
The digital transformation within religious courts through the e-Court system represents a strategic step toward realizing efficient and accessible legal services, particularly in cases of Islamic family law. This system offers administrative conveniences such as e-filing, e-payment, and online hearings. However, the substantive effectiveness of e-Court still faces multiple challenges, including technological access gaps, limited legal literacy, and normative obstacles in aligning sharia values with digital procedures. This study evaluates the extent to which the e-Court system ensures substantive justice, especially for vulnerable groups such as women and children. Using a normative approach, the article emphasizes the importance of integrating Islamic justice principles such as al-‘adalah (justice) and al-mashlahah (public interest) within digital judicial governance. The findings show that although e-Court improves procedural efficiency, it has yet to fully address the complex emotional and spiritual dimensions of family disputes. Therefore, a more inclusive regulatory and ethical framework is needed to ensure that digitalization does not create new inequalities in access to justice.